Efficacy of continuous epidural anesthetics and steroids infusion for management of acute herpes zoster and postherpetic neuralgia: a retrospective study - Dou, Xinyu; Guan, Xinghai; Li, Chen; Qin, Wangjun; Zhang, Yi; Li, Yifan; Han, Bingyu; Wu, Chenglong; Chen, Yangyang; Wang, Li; Mao, Peng; Zhou, Ling; et al. (Frontiers in Neurology, 2025)
BackgroundHerpes zoster (HZ), caused by the reactivation of the varicella-zoster virus, frequently leads to postherpetic neuralgia (PHN), a debilitating neuropathic pain condition. Current treatments for acute HZ and PHN prevention remain suboptimal. This study evaluates the efficacy of continuous epidural infusion of anesthetics and steroids combined with conventional oral medication management (epidural infusion group) vs. conventional oral medication management (contrast group) alone in managing acute HZ and reducing PHN incidence.MethodsA retrospective analysis included 173 acute HZ patients [numerical rating scale (NRS) score ≥4] treated with epidural infusion group (n = 89) or contrast group (acyclovir, mecobalamin, and vitamin B1; n = 84). Epidural infusion group combined lidocaine (0.25%−0.5%, 0.5 ml/h) and betamethasone (0.3 ml/day) administered via epidural catheter for 3 days. Outcomes assessed skin lesion recovery, pain relief (NRS scores), PHN incidence, complications, and patient satisfaction over 3 months.ResultsEpidural infusion group significantly improved skin lesion recovery (88.43 vs. 79.33% at 1 month, P < 0.001) and rash elimination (98.76 vs. 96.67% at 1 month, P = 0.039). Pain scores were lower in the epidural infusion group at all follow-ups (3 days to 3 months, P < 0.05). PHN incidence at 3 months was reduced with epidural infusion group (11.2 vs. 23.8%, P = 0.028), with higher complete remission rates (82.0 vs. 61.9%, P = 0.003). Complication rates were comparable between groups (P > 0.05), and patient satisfaction scores favored epidural infusion group (3.68 ± 1.01 vs. 4.18 ± 0.83, P < 0.001).ConclusionEpidural infusion group demonstrates superior efficacy in alleviating acute HZ symptoms, accelerating skin healing, and reducing PHN risk compared to oral therapy, with comparable safety and higher patient satisfaction. This approach offers a promising strategy for HZ management, warranting further validation through large-scale prospective trials.